Historical Development, Preparation, Characterization, and Pharmacokinetics of Nanoparticles: A Review - Kalita, Mr. Pratap (Asian Journal of Pharmaceutics (AJP), 2019)
In recent years, there has been a considerable research interest in the development of novel drug delivery systems using nanoparticles (NPs) as a drug carrier for small and large molecules. The development of nanoscale carriers is capable of delivering that the active drug has the potential to overcome both systemic and different barriers and also provides specific, sustained, and targeted delivery at the site of action for therapeutic potency. The conventional drug therapies are having some limitations, and they produce fluctuations in plasma drug levels. Conventional drug therapies do not provide linear and sustained action compared to NPs in general. Nanonization technologies established a commercial matured drug delivery platform. Nanotechnology has attained specific importance and platform due to a steadily increase in number of the development of compounds showing poor aqueous solubility. The NPs consist of pure active pharmaceutical ingredients, and these particles are often stabilized with surfactants, and polymeric stabilizers adsorbed onto their surface. The nanoparticulate drug delivery system mainly includes nanoemulsion, nanosuspension, liposomes, nanoimplants, lipid, or polymeric NPs. NPs have been improving the therapeutic effect of drugs and minimize the side effects. The present review paper comprised the advantages and disadvantages, formulation aspects and characterization of NP as drug delivery system.